National development level effects on capital budgeting practices: a comparative study of nature vs nurture - Pratheepkanth, P. (Emerald Publishing Limited, 2022)
Purpose – This research should help determine whether development should focus on individual firms or will raising the national development level act like a rising tide and raise the performance of all corporations. Design/methodology/approach – The comparative data used in this study come from 150 Australian (ASX200 index listed) firms and 150 Sri Lankan (Colombo Stock Exchange listed) firms. The research questions are answered via a quantitative research design that uses primary and secondary data. Findings – The findings demonstrate that capital budgeting practices are more influenced by contingency features and sophistication in Australia and Sri Lanka. Also, Australian firms tend to use capital budget models with good-to-strong predictive power (except for ROE) and Sri Lankan firms tend to use capital-budget models with fair-to-poor predictive power. Further, the analysis of Australian firms yielded much stronger and more statistically significant results than the analysis of Sri Lankan firms. Practical implications – In complex real-world situations, reconciling the outputs of a multifaceted approach to capital budgeting methods is more likely to give the depth and width of input needed to achieve an optimal capital investment plan. Originality/value – The results of this study can provide rich information for stakeholders about new findings in capital budgeting (CB) practices and their contributions to firm performance in a comparative perspective
Keywords: Capital budgeting; Discounted cash flow; Non-discounted cash flow